Frecuencia de mutaciones inducidas por el metanosulfato de etilo en semillas de frijol común (Phaseolus vulgaris L.) en diferentes estados de germinación - Delgado de la Flor, L.F.; Moh, C.C; Alan, J.J. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Experiments were performed to determine which period of seed germination is most sensitive to EMS treatment for inducing mutations in two varieties of beans (Turrialba 1 and Porrillo). It was found that when the treatment was applied at or after 24 hours of seed germination (at 20OC), the induced mutation frequencies were higher than those when the same treatment was applied before 24 hours. Therefore, 24 hours of seed germination is an appropriate period for applying the mutagen for inducing a high mutation frequency. In addition, It also has the following advantages: 1) because of this sensitive period, the mutagen can be used more economically and thus less hazardously; 2) it permits the selection of seeds with uniform growth for the experiments; and 3) it serves as a very convenient working schedule for applying the mutagenic treatment.